Answer:
(x + 4)² + (y + 1)² = 4
Explanation:
From the graph attached,
Extreme ends of the diameter of the circle,
(-4, 1) and (-4, -3)
Center of the circle = Midpoint of the diameter
Center =

=

= (-4, -1)
Radius of the circle = Distance between the center and extreme end
= 2 units
Since standard equation of the circle is,
(x - h)² + (y - k)² = r²
where (h, k) is the center and 'r' is the radius of the circle
By substituting the values in the standard equation,
(x + 4)² + (y + 1)² = 2²
(x + 4)² + (y + 1)² = 4